Mycosis fungoides in a 15-year-old adolescent - Sarah Estelmann; Anna Neuberger; Ferdinand Toberer; Christine Fink; Alexander Enk; Holger Andreas Haenssle (Mattioli1885, 2018)
Not applicable (Case letter)